PEMANFAATAN SUMBER DAYA AIR SUNGAI BATAS NEGARA DI DESA ALAS SELATAN KECAMATAN KOBALIMA TIMUR - Amaral, Maria Hermalinda Soi; Jonathan, Koehuan; Dethan, Jemmy J. S. (Universitas Nusa Bangsa, 2025)
Currently, attention is increasing on the management of border rivers, particularly in ASEAN member countries. A large portion of the border between Indonesia and Timor-Leste is river-bound, and communities are highly active in exploiting its potential. However, studies on river resource utilization in the border region between Indonesia and Timor-Leste are still very rare. Therefore, this study aims to analyze the relationship between community social characteristics, perceptions of river utilization, and analysis of the physical condition of the river. This research was conducted on the Motamasin River in Alas Selatan Village, on the Indonesia-Timor Leste border. A mixed methods approach was used, combining quantitative data in the form of social surveys and river discharge measurements with qualitative data from community perceptions through interviews and field observations. The results indicate that the majority of the community is of productive age and has a secondary or higher education level, which supports their understanding of the importance of sustainable water management. The Motamasin River is predominantly used for household and agricultural purposes, while fisheries use is still limited due to water quality degradation. The river's morphology exhibits intermittent characteristics with significant discharge fluctuations, ranging from 100 to 400 m³/s. These findings emphasize the importance of an interdisciplinary approach to water resource management that simultaneously considers social and physical aspects, especially in vulnerable border areas that have not been optimally served by national development policies.